Long-term Complications of Unintentional Dural Puncture During Labor Epidural Analgesia: A Case–control Study. Issue 1 (22nd March 2023) - Lacombe, A.; Downey, K.; Ye, X.Y.; Carvalho, J.C.A.
Abstract : ( Reg Anesth Pain Med . 2022;47:364–369) Despite epidural labor analgesia use being widespread, unintentional dural puncture (UDP) occurs at a rate of 0.5% to 1.5% depending on the type of institution (training vs. nontraining). The short-term adverse outcome—postural postdural puncture headache (PDPH), and associated nausea, vomiting, auditory disturbances, visual disturbances, neck stiffness, and reduced ADLs may resolve with conservative management. If these adverse outcomes do not resolve with conservative management, lumbar epidural blood patch (EBP) is considered the definitive treatment. Anecdotally, UDP may lead to long-term complications, but published data for long-term follow-up is lacking. The aim of this study is to investigate whether laboring women who experienced an UDP were at risk for developing long-term complications and to investigate whether EBP influences outcomes.